2021
DOI: 10.18196/jai.v22i1.10318
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Dimensions and Sustainable Stock Exchanges Returns in the Asian Region

Abstract: Research aims: The aim of this paper is to examine the effect of four cultural dimensions such as power distance index (PDI), individualism (IDV), uncertainty avoidance index (UAI), and long-term orientation (LTO) on the sustainable investment return in Asian sustainable stock exchanges.Design/Methodology/Approach: Quantitative research method was applied for this research. Monthly sustainable stock indices from seven Asian countries for the period 2015-2019 were considered. This research employed the Ordinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
1
12
1
Order By: Relevance
“…The research demonstrates that the Uncertainty Avoidance Index does not affect stock returns. This result reflects the research of Darsono et al (2021), which found a positive coefficient for UAI but does not support the study which states that UAI has a positive impact on sustainable stock returns in the Asian region. The countries studied are evenly divided between countries with significant UAI scores and countries with more minor UAI scores, with 50% of countries in the Asian region and 80% of countries in the European region having significant UAI scores.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The research demonstrates that the Uncertainty Avoidance Index does not affect stock returns. This result reflects the research of Darsono et al (2021), which found a positive coefficient for UAI but does not support the study which states that UAI has a positive impact on sustainable stock returns in the Asian region. The countries studied are evenly divided between countries with significant UAI scores and countries with more minor UAI scores, with 50% of countries in the Asian region and 80% of countries in the European region having significant UAI scores.…”
Section: Discussioncontrasting
confidence: 99%
“…The results of the research show that IDV does affect stock returns. This result supports the research of Darsono et al (2021), which states that IDV positively impacts sustainable stock returns in the Asian region. The majority of the studied countries have low IDV scores, indicating that most of them are collectivist countries.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this context, the role of government emerges as the driver of the economy with fiscal and monetary instruments. Nevertheless, considerable diversity exists among the ASEAN Member States regarding their economic, social, and cultural development (Darsono et al, 2021). The size and scope of this diversity pose challenges to analyzing ASEAN as a single, homogenous bloc of nations.…”
Section: Introductionmentioning
confidence: 99%